USING EDUCATIONAL MARBLE GAMES IN GERMAN LANGUAGE TEACHING - COŞKUN, HASAN (Journal of Education Culture and Society, 2020)
The aim of this article is to show how German students can be motivated by learning games. Apart from the development and didacticisation of the learning game “Marbles”, the attitude of  Turkish families and language teaching educational establishments and the support of the DaF lessons by German mediating institutions in Turkey will be considered. The attitude of Turkish families to learning foreign languages is mostly positive. Turkish educational authorities and those responsible for education take various measures to expand foreign language teaching availability in the schools. German institutions which provide teachers (Goethe-Institut, ZfA, DAAD) promote the improvement of German teaching in Turkey. Nevertheless, the quality of German teaching is not satisfactory mostly because the available teachers are not adequately qualified, teacher training is remote from practice, the quality of text books and teaching materials, the traditions of learning, the excessively large classes, inadequate learning environment (language cabinets and equipment), the nature and method of central examinations (multiple choice) and their significance in the Turkish educational system. In the long-term, this leads to frustration in both teachers and students. The Turkish educational authorities initially took measures to expand the availability of language teaching in the course of harmonisation of the Turkish educational system to that of the EU e.g. the introduction of a second foreign language. German mediating institutions ensure reasonable further training for teachers locally and in Germany and support the creation of teaching materials etc.The Ministry of Education in Turkey, has started to take measures for students to learn other languages such as German, French, Russian, Spanish, Japanese, Italian, Arabic, ethnic languages ​​in Turkey, et cetera in the educational institutions in addition to English. For example, in the Anatolian high schools two foreign languages are taught.  The Board for Higher Education in Turkey, has introduced second foreign language lessons in  foreign language teacher programs, envisioned to be taken for three semesters, in order for the language teachers to gain experience in the field of two languages.  Private education institutes are emphasizing that they are teaching more than one foreign language in order to draw more students. Families make an economic sacrifice for their children in order for them to learn foreign languages. It is observed that in some districts of certain major cities, teaching of foreign languages has started to be given as early as at kindergarten level. In Turkey, German is preferred as the second foreign language in general. Nowadays, German is the second preferred language from primary to high school in Turkey. The quality of German language lessons should be increased for more students to select German as the second foreign language in the coming years. Despite all these efforts, teaching foreign language is not up to the desired level in Turkey (Bayraktaroğlu, 2014, pp. 9-14; Demircan, 2014, pp. 17-22). For that reason, it is important that motivating teaching methods and teaching materials be developed for German teaching.